Mucosa-Associated Lymphoid Tissue Lymphoma Translocation Protein 1 Positively Modulates Matrix Metalloproteinase-9 Production in Alveolar Macrophages upon Toll-Like Receptor 7 Signaling and Influenza Virus Infection - Lee, Yu-Hsiang; Huang, Juin-Hua; Chang, Tzu-Hsuan; Yang, Hung-Chih; Wu-Hsieh, Betty A. (Frontiers in Immunology, 2017)
Influenza A virus (IAV) infection causes significant morbidity and mortality worldwide. Matrix metalloproteinase-9 (MMP-9) degrades extracellular matrix and is involved in the pathology of influenza. It has been reported that MMP-9 mediates neutrophil migration in IAV infection. Whether alveolar macrophages, the first immune cells that encounter IAV, produce MMP-9 and the mechanism of its regulation have never been investigated. As Toll-like receptor 7 (TLR7) is one of the receptors in innate immune cells that recognizes IAV, we used TLR7 agonists and IAV to stimulate alveolar macrophage MH-S cells, primary macrophages and bone marrow neutrophils. Results showed that MMP-9 expression in macrophages is inducible by TLR7 agonist and IAV, yet MMP-9 production by neutrophils is not inducible by either one of them. We hypothesized that MMP-9 production in macrophages is mediated through TLR7-NF-κB pathway and used microarray to analyze TLR7 agonist-induced NF-κB-related genes. Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1), a positive regulator of NF-κB, is amongst the top highly induced genes. By use of MALT1 inhibitor (z-VRPR-fmk) and alveolar macrophages from MALT1-deficient mice, we found that MMP-9 production is MALT1-dependent. While MALT1 can act as a paracaspase in lymphocytes through degrading various signaling proteins, we discovered that MALT1 functions to reduce a negative regulator of NF-κB, cylindromatosis (CYLD), in alveolar macrophages. IAV-induced MMP-9, TNF and IL-6 in lungs of MALT1-deficient mice are significantly lower than in wild-type mice after intratracheal infection. MALT1-deficient mice also have less body weight loss and longer survival after infection. Taken together, we demonstrated a novel role of MALT1 in regulating alveolar macrophage MMP-9 production whose presence exacerbates the severity of influenza.